Downregulation of prostaglandin E receptor subtype EP3 during colon cancer development. Issue 8 (9th July 2004) - Shoji, Y; Takahashi, M; Kitamura, T; Watanabe, K; Kawamori, T; Maruyama, T; Sugimoto, Y; Negishi, M; Narumiya, S; Sugimura, T; Wakabayashi, K
Abstract : Background and aims: Involvement of prostaglandin E2 (PGE2 ) receptors EP1, EP2, and EP4 in the formation of aberrant crypt foci (ACF) and/or intestinal polyps has been suggested. In contrast, EP3 appears to have no influence on the early stages of colon carcinogenesis. In the present study, we examined expression of PGE2 receptor subtypes EP1, EP2, EP3, and EP4 in normal colon mucosa and colon cancers, and assessed the contribution of EP3 to colon cancer development. Methods: mRNA expression of PGE2 receptor subtypes EP1, EP2, EP3, and EP4 in normal colon mucosa and colon cancers in azoxymethane (AOM) treated mice and rats, and in humans, were examined by reverse transcription-polymerase chain reaction (RT-PCR), quantitative real time RT-PCR, and immunohistochemical analyses. Evaluation of the role of EP3 was performed by intraperitoneal injection of AOM, using EP3 receptor knockout mice. Effects of EP3 receptor activation on cell growth of human colon cancer cell lines were examined using ONO-AE-248, an EP3 selective agonist. Moreover, EP3 expression in colon cancer cell lines was analysed with or without 5-aza-2′-deoxycytidine (5-aza-dC) treatment. Results: Expression levels of EP1 and EP2 mRNA were increased in cancer tissues. EP4 mRNA was constantly expressed in normal mucosa and cancers. In contrast, expression of EP3 mRNA was markedly decreased in colon cancer tissues, being 5% in mice, 9% in rats, and 28% in humans compared with normal colon mucosa, analysed by quantitative real time RT-PCR. Immunohistochemical staining demonstrated the rat EP3 receptor protein to be expressed in epithelial cells of normal mucosa and some parts of small carcinomas but hardly detectable in large carcinomas of the colon. Colon cancer development induced by AOM in EP3 receptor knockout mice was enhanced compared with wild-type mice, with a higher incidence of colon tumours (78% v 57%) and mean number of tumours per mouse (2.17 (0.51) v 0.75 (0.15); p<0.05). Expression of EP3 mRNA was detected in only one of 11 human colon cancer cell lines tested. Treatment with 5 μM of an EP3 selective agonist, ONO-AE-248, resulted in a 30% decrease in viable cell numbers in the HCA-7 human colon cancer cell line in which EP3 was expressed. Treatment with 5-aza-dC restored EP3 expression in CACO-2, CW-2, and DLD-1 cells but not in WiDr cells, suggesting involvement of hypermethylation in the downregulation of EP3 to some extent. Conclusion: The PGE2 receptor subtype EP3 plays an important role in suppression of cell growth and its downregulation enhances colon carcinogenesis at a later stage. Hypermethylation of the EP3 receptor gene could occur and may contribute towards downregulating EP3 expression to some extent in colon cancers.